2008
DOI: 10.1038/nm.1900
|View full text |Cite
|
Sign up to set email alerts
|

γ-secretase inhibitors reverse glucocorticoid resistance in T cell acute lymphoblastic leukemia

Abstract: Summary Gamma-secretase inhibitors (GSIs) block the activation of oncogenic NOTCH1 in T-cell acute lymphoblastic leukemia (T-ALL). However, limited antileukemic cytotoxicity and severe gastrointestinal toxicity have restricted the clinical application of these targeted drugs. Here we show that combination therapy with GSIs plus glucocorticoids can improve the antileukemic effects of GSIs and reduce their gut toxicity in vivo. Inhibition of NOTCH1 signaling in glucocorticoid-resistant T-ALL restored glucocortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
383
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(396 citation statements)
references
References 46 publications
11
383
2
Order By: Relevance
“…34 This combination treatment improved anti-leukemic effects and reduced their gut toxicity in vivo. 34 Similarly, glucocorticoid treatment is part of the polychemotherapy regimens used in cHL, and might be tested in future studies in combination with GSI for treatment of lymphoma patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…34 This combination treatment improved anti-leukemic effects and reduced their gut toxicity in vivo. 34 Similarly, glucocorticoid treatment is part of the polychemotherapy regimens used in cHL, and might be tested in future studies in combination with GSI for treatment of lymphoma patients.…”
Section: Discussionmentioning
confidence: 98%
“…33 GSI treatment was hampered by severe gastrointestinal toxicity and limited anti-leukemic efficacy. 34 However, a study in mice showed very promising results when using GSI in combination with glucocorticoids in T-ALL. 34 This combination treatment improved anti-leukemic effects and reduced their gut toxicity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, glucocorticoids, which are widely used for T-ALL treatment are well-known, although non-specific, NFκB inhibitors 29 and it has been previously published that combination of GSI and glucocorticoids is effective on leukemic treatment in mice models while reducing the intestinal toxicity effects of Notch inhibition. 30 In addition, the proteasome inhibitor bortezomib, which is also a well-known NFkB inhibitor, is used for the treatment of multiple myeloma and mantle cell lymphoma. 31 In summary, we here show that Hes1 directly represses CYLD promoter and that Hes1 activation and CYLD repression are both obligatory events to maintain predominant role in maintaining T-ALL in vivo.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Although gastrointestinal side effects have been reported for g-secretase inhibitor administration in mice, we did not observe any overt side effects of DAPT administration at this dose. 16 Histological and Immunofluorescence Analyses These rats were anaesthetized by the method as described earlier, and the venous grafts of rats were harvested at the given time point. Grafts were obtained by cutting the transplanted segments from the native vessels at the cuff end.…”
Section: Materials and Methods Animal Studiesmentioning
confidence: 99%